2017
DOI: 10.1177/0895904817736631
|View full text |Cite
|
Sign up to set email alerts
|

Holistic School Quality Measurement and the Future of Accountability: Pilot-Test Results

Abstract: School accountability systems in the United States have been criticized on a number of fronts, mainly on grounds of completeness and fairness. This study examines an alternative school quality framework—one that seemingly responds to several core critiques of present accountability systems. Examining results from a pilot study in a diverse urban district, we find that this alternative system captures domains of school quality that are not reflected in the current state system, specifically those measuring oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…HSIs can further assess the empowerment Latinx students may encounter through their experiences directly and indirectly associated with grant activities (Cuellar et al, 2017). Integrating these liberatory and empowering experiences and outcomes align with recent calls in K-12 accountability systems to include student voice and institutional climate measures (Gagnon & Schneider, 2019;Schneider et al, 2021) and adopting them into higher education.…”
Section: Institutionsmentioning
confidence: 77%
“…HSIs can further assess the empowerment Latinx students may encounter through their experiences directly and indirectly associated with grant activities (Cuellar et al, 2017). Integrating these liberatory and empowering experiences and outcomes align with recent calls in K-12 accountability systems to include student voice and institutional climate measures (Gagnon & Schneider, 2019;Schneider et al, 2021) and adopting them into higher education.…”
Section: Institutionsmentioning
confidence: 77%
“…'Professional accountability' is characterised by the adherence to professional norms, local management, state regulations related to teacher training and working conditions, and accountability with peers (Falabella & de la Vega, 2016). A professional accountability approach based on expertise and the collaborative work of teachers who are accountable to their local school community (Carrasco et al, 2015;Falabella, 2019;Sahlberg, 2010), or an accountability approach focused on schools' "opportunities to learn", instead of schools' outcomes (Gagnon & Schneider, 2017) might prove a more fruitful approach in both countries and enhance teacher autonomy. Finding more constructive ways of holding teachers accountable whilst giving them the autonomy to be creative, is an essential ingredient in building a more deeply conceptualised form of education where both teachers and pupils are engaged with and enjoy their experience of and contribution to education.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from existing survey instruments, these scales offer strong evidence of validity and had been previously tested for reliability (Gagnon & Schneider, 2019). Scales were piloted for 2 years in a highly diverse district.…”
Section: Methodsmentioning
confidence: 99%
“…One study, for instance, found that various elements of school quality may be orthogonal. Investigating five measured categories of school quality, Gagnon and Schneider (2019) found only moderate correlations—indicating that student standardized test scores would not be predictive of other valued processes and outcomes. Other research has found that, even within bounded domains of quality, variation exists.…”
Section: Conceptual Framework and Relevant Literaturementioning
confidence: 95%